A 2-year follow-up analysis of individuals with internet use disorders treated with the webcam-based telemedicine OMPRIS intervention - Jan Dieris-Hirche; Sebastian Nikofor; Magdalena Pape; Laura Bottel; Martin Diers; Bert Theodor te Wildt; Klaus Wölfling; Peter Henningsen; Anja Neumann; Rainer Beckers; Stephan Herpertz; Nina Timmesfeld (Scientific Reports)
Abstract Evidence-based online treatments for internet use disorders (IUD) are poorly studied. The online-based, therapist-guided, motivational intervention program for internet use disorder (OMPRIS) has shown significant effects on reducing IUD symptoms, while the symptoms remained high in the waiting control group. The current study presents a 2-year follow-up analysis of the IUD symptoms. Participants in the OMPRIS study were followed up 2 years after the intervention. The primary outcome was a reduction in IUD symptoms. Secondary outcomes were time spent on the internet, depression and anxiety symptoms, and general life satisfaction. Linear mixed models (LMMs) were performed to assess the outcomes over time across the intervention and three follow-up measurement, controlling for the covariates age and gender. A total of 116 out of 180 OMPRIS participants (64.4%) were reached for the follow-up survey after 2 years. The LMM showed no significant increase in IUD symptom severity across all three follow-up measurements relative to post treatment measurements. Age and gender had no significant influence in the model. Similar results were found for all secondary outcomes. According to this study, IUD can be effectively treated via webcam and is therefore suitable for patients who are unable or unwilling to undergo face-to-face psychotherapy.